Encyclopedia of biometrics - Li, Stan Z. (Springer, 2009)
Biometrics refers to automated methods of recognizing a person based on physiological or behavioral characteristics. The Encyclopedia of Biometrics provides a comprehensive reference to topics in Biometrics, including concepts, modalities, algorithms, devices, systems, security, performance testing, applications and standardization. With an A–Z format, the Encyclopedia of Biometrics provides easy access to relevant information on all aspects of biometrics for those seeking entry into this broad field. The Encyclopedia is composed of approximately 250 overview entries, and 800 definitional entries. Each entry includes a definition, key words, list of synonyms, list of related entries, illustration(s), applications, and a bibliography. Most entries include useful literature references providing the reader with a portal to more detailed information. The style of the entries is expository and tutorial, making the encyclopedia a practical resource for experts in the field and professionals in other fields. Editorial board. list of contributors. Preface. A-Z entries with references - General issues. Biometrics. Sensors and devices. Pattern Recognition. Data fusion. Performance evaluation - Modalities. Face. Fingerprint. Iris. Hand. Vein. Signature. Speaker. Gait. Ear - Other modalities. Keystroke, Lip movement, EEG, Odor, Skull, Teeth, DNA. Sample synthesis - Systems and applications. System design. Security. Applications. Forensic science. Standardization - Index.